2016
DOI: 10.1681/asn.2015070827
|View full text |Cite
|
Sign up to set email alerts
|

Dichloroacetate Prevents Cisplatin-Induced Nephrotoxicity without Compromising Cisplatin Anticancer Properties

Abstract: Cisplatin is an effective anticancer drug; however, cisplatin use often leads to nephrotoxicity, which limits its clinical effectiveness. In this study, we determined the effect of dichloroacetate, a novel anticancer agent, in a mouse model of cisplatin-induced AKI. Pretreatment with dichloroacetate significantly attenuated the cisplatin-induced increase in BUN and serum creatinine levels, renal tubular apoptosis, and oxidative stress. Additionally, pretreatment with dichloroacetate accelerated tubular regener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 83 publications
4
37
0
Order By: Relevance
“…Lipo‐3cis and 3cis , however, demonstrated significant attenuation of NOX4 and TNF‐α levels over that of the CDP‐treated group. Previously, it was reported that DCA was able to preserve the renal functions when used in conjunction with CDP, thereby supporting our observations …”
Section: Methodssupporting
confidence: 92%
“…Lipo‐3cis and 3cis , however, demonstrated significant attenuation of NOX4 and TNF‐α levels over that of the CDP‐treated group. Previously, it was reported that DCA was able to preserve the renal functions when used in conjunction with CDP, thereby supporting our observations …”
Section: Methodssupporting
confidence: 92%
“…The mice were challenged with cisplatin (an antineoplastic drug) at a reported nephrotoxic dosage (intraperitoneal injection, 20 mg kg –1 bw). [ 35 ] The control mice were treated with saline or protected with N ‐acetyl‐l‐cysteine (NAC, i.v. injection, 400 mg kg –1 bw) 0.5 h prior to cisplatin challenge, and real‐time imaging was conducted at t dpt = 48 h. [ 36 ] NAC was reported to be able to attenuate kidney damage by reducing oxidative stress and alleviating kidney inflammation in mouse model.…”
Section: Figurementioning
confidence: 99%
“…Thereafter, similar to real‐time imaging, FPRR‐based urinalysis noninvasively detected AKI at 24 h post‐cisplatin treatment, which was 48 h earlier than reported detection time points for elevated serum creatinine and kidney tissue injury ( t dpt = 72 h). [ 35 ]…”
Section: Figurementioning
confidence: 99%
“…The combination of CQ with biguanide metformin entered a clinical trial for patients with solid tumors bearing mutations in the IDH1 and IDH2 genes. 261 Their effectiveness in pH regulation of the tumor microenvironment will still need to be empirically determined. These gliomas had shown a decreased capacity to generate an acidic extracellular microenvironment, an effect, however, that cannot be generalized.…”
Section: Feasibility Of Treating Malignant Tumors With Cq: Strengthsmentioning
confidence: 99%
“…260 One potential solution to decrease tissue acidity is the use of inhibitors of glycolytic flux such as dichloroacetate, which might inhibit acidosis without compromising cancer treatment. 261 Their effectiveness in pH regulation of the tumor microenvironment will still need to be empirically determined.…”
Section: Feasibility Of Treating Malignant Tumors With Cq: Strengthsmentioning
confidence: 99%